Family caregivers' experiences of interaction with people with mild‐to‐moderate dementia in China: A qualitative study. Issue 4 (23rd September 2020) - Yang, Lili; Ye, Huiling; Sun, Qiuhua
Abstract: Aim: This study aimed to explore the experiences of family caregivers interacting with people with dementia. Background: A majority of people with mild‐to‐moderate dementia live at home with family caregivers. This interaction creates positive experiences and challenges for these caregivers. Design: Descriptive phenomenological qualitative inquiry guided this study. Methods: This qualitative study involved semi‐structured interviews with the caregivers of people with mild‐to‐moderate dementia ( n = 10). Data were collected from June to September 2018, and then data were thematically analysed. Results: Six categories of themes were identified from the interviews: (1) unexpected things often happen; (2) positive coping strategies; (3) sense of accomplishment because people with dementia actively participate in activities; (4) sense of frustration because of the reluctance of people with dementia to participate in activities; (5) hope for the happiness of people with dementia; and (6) want to have their own life. Conclusions: This study reveals that caregivers could positively interact with people with dementia through creating opportunities and arranging meaningful activities. Future research should focus on family management and training on how to help caregivers interact effectively with people with dementia. SUMMARY STATEMENT: What is already known about this topic? A majority of people with mild‐to‐moderate dementia live at home with family caregivers. Many caregivers suffer from depression, anxiety, fatigue, insomnia, family conflicts and low levels of life satisfaction. How caregivers interact with people with dementia at home remains unclear. What this paper adds? Caregivers experience various feelings, such as a sense of accomplishment and occasionally frustration, when interacting with people with dementia. Caregivers stated that they wanted people with dementia to be happy and live their life. Thus, the caregivers changed their attitude, accepted the situation and organized meaningful activities for people with dementia. Caregivers employed various strategies for handling situations involving people with dementia and shared how they interacted with such individuals. The implications of this paper: Care organizations that can offer certain services for people with dementia should be developed to lessen caregivers' burden. Community nurses should develop caregivers' strengths and enhance their abilities to improve interaction with people with dementia. Future research should focus on family management and training on how to help caregivers interact effectively with people with dementia.